Integrative review of the influence of strength training on sarcopenia in the elderly (Research, Society and Development, 2022)
The progressive loss of muscle mass characterizes Sarcopenia, being increasingly accentuated with the progression of age, providing numerous other health problems triggered by sarcopenia. The present study deals with an integrative review of literature sportively aimed at evaluating the benefits of strength training in the staging and regression of sarcopenia in the elderly, published between 2009 and 2021, available in Portuguese, English. Articles available in the PubMed database were selected, and approach research was taken into account for the study of controlled and randomized tests, meta-analyses and clinical trials. To evaluate methodological quality, the adapted Critical Appraisal Skill Programme (CASP) was used, which covered 10 items to be analyzed. Sarcopenia has a more frequent prevalence in people over 60 years of age with strength training as one of the most efficient methods of combat. In addition, it also involves improving life for the elderly affected by this disease.